Modelling and Simulation of Diffusive Processes Methods and Applications - Basu, S.K; Kumar, Naveen (Simulation Foundations, Methods and Applications, 2014)
Computer simulation and mathematical modelling are the most important approaches in the quantitative analysis of the diffusive processes fundamental to many physical, chemical, biological, and geological systems. This comprehensive text/reference addresses the key issues in the Modelling and Simulation of Diffusive Processes from a broad range of different application areas. Applying an holistic approach, the book presents illuminating viewpoints drawn from an international selection of experts across a wide spectrum of disciplines, from computer science, mathematics and engineering, to natural resource management, environmental sciences, applied geo-sciences, agricultural sciences, and theoretical medicine. Topics and features: Presents a detailed introduction to diffusive processes and modelling Discusses diffusion and molecular transport in living cells, and suspended sediment in open channels Examines the mathematical modelling of peristaltic transport of nanofluids, and isotachophoretic separation of ionic samples in microfluidics Reviews thermal characterization of non-homogeneous media, and scale-dependent porous dispersion resulting from velocity fluctuations Describes the modelling of nitrogen fate and transport at the sediment-water interface, and groundwater flow in unconfined aquifers Investigates two-dimensional solute transport from a varying pulse type point source, and futile cycles in metabolic flux modelling Studies contaminant concentration prediction along unsteady groundwater flow, and modelling synovial fluid flow in human joints Explores the modelling of soil organic carbon, and crop growth simulation This interdisciplinary volume will be invaluable to researchers, lecturers and graduate students from such diverse fields as computer science, mathematics, hydrology, agriculture and biology.